Teacher Challenges in Teaching Writing Skills through Merdeka Curriculum in SMAN 1 Pabedilan - Hafifah Putri Hasani; Fitri Aprianti; Ikariya Sugesti (Proceedings Series on Social Sciences & Humanities, 2024)
Merdeka curriculum is a curriculum approach intoduced in Indonesia to provide more flexibility to schools and teachers who design and implement the education curriculum. This research aims to find out the challenges faced by teachers in teaching writing skills through merdeka curriculum. This study explores the various challenges teachers face. This research article uses a qualitative descriptive method. The data in this study were obtained by conducting an interview with an English teacher at SMAN 1 Pabedilan. The findings show that the biggest challenge in implementing merdeka curriculum, especially in teaching writing is adjusting the diversity of students’ ability levels and teacher lacks undertanding in using technology. Based on the findings, teachers need to take a more in-depth approach to determine students’ abilities and schools are advised to organize training for teachers on effective strategies and methods of teaching writing. This training should include the use of technology, creative appproaches and assessment methods in accordance with merdeka curriculum.